Cu0.5Zn0.5Fe2O4 ferrite for application as a soft magnetic material - Costa, A. C F M; Costa-Jr, A. D S; Viana, K. M S; Portela, F. A.; Paiva-Santos, C. O. [UNESP]; Kiminami, R. H G A (Trans Tech Publications, 2012)
This work involved the synthesis and characterization of Cu0.5Zn0.5Fe2O4 ferrite powders prepared by combustion reaction for use as soft magnetic materials. The powders were characterized by nitrogen adsorption (BET), XRD, Rietveld refinement, SEM, TEM and magnetic measures. The results indicate that the combustion reaction yielded crystalline powders containing spinel ferrite as the primary phase and traces of Fe2O3 as secondary phase. The crystallite size and lattice microdeformation calculated from Rietveld refinements were 36 and 0.24 nm, respectively. The micrographic analysis revealed particles smaller than 100 nm and fine particle agglomerates. The particles were approximately spherical and their size, calculated by TEM, was 29 nm. The magnetic parameters indicated that the Cu-Zn ferrite powders presented closed hysteresis loops and soft magnetic properties. © (2012) Trans Tech Publications, Switzerland.
Keywords: Combustion reaction; Cu-Zn ferrites; Nanoparticles; Soft magnetic material; Combustion reactions; Crystalline powder; Ferrite powders; Fine particles; Magnetic measures; Magnetic parameters; Microdeformations; Micrographic analysis; Nitrogen adsorption; Primary phase; Secondary phase; Soft magnetic properties; Spinel ferrites; XRD; Combustion; Ferrite; Ferrites; Gas adsorption; Magnetic properties; Powders; Rietveld refinement; Soft magnetic materials; Synthesis (chemical); Zinc